Exome Sequencing Analysis on Products of Conception: A Cohort Study to Evaluate Clinical Utility and Genetic Etiology for Pregnancy Loss. Issue 8 (August 2021) - Zhao, Chen; Chai, Hongyan; Zhou, Qinghua; Wen, Jiadi; Reddy, Uma M.; Kastury, Rama; Jiang, Yonghui; Mak, Winifred; Bale, Allen E.; Zhang, Hui; Li, Peining
Abstract : (Abstracted from Genet Med 2021;2:435–442) Genetic variants are known to cause pregnancy loss. New data from exome sequencing studies have reported that exome sequencing may be a useful tool in identifying causes of pregnancy loss.